PENGELOLAAN MEDIA SOSIAL INSTAGRAM DALAM MEMBANGUN BRAND IMAGE PONDOK PESANTREN TAHFIDZUL QUR'AN AZIZIYYAH - Aziz, Naufal Abdul; Ardianto, Irwan; Nugraha, Aditya; Kurniasari, Ni Gusti Ayu Ketut (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
PPTQ Aziziyyah is one of the Islamic boarding schools in Tangerang. Arabic and English are the languages used by PPTQ Aziziyyah students. This aims to improve the quality of students in the fields of knowledge and communication skills where the students and female students here not only excel in memorizing Allah's verses, but are also fluent in international Arabic and English. The research method used in this research is a case study with a qualitative approach through focus group discussions. The research uses a critical paradigm. The data collection technique uses a focus group discussion involving resource persons from the Tahfidzul Qur'an Aziziyyah Islamic Boarding School, namely teaching staff. The results of this research aim to find out how the Instagram social media management team at Tahfizdzul Qur'an Aziziyyah Islamic Boarding School manages the brand image on Tahfidz Instagram to become an advantage as a selling point, content characteristics as determinants in content formation, maximizing the features and potential of the Instagram application and engagement such as the number of likes, views and followers as indicators of success in building the brand image of the Pondok Pesantren Tahfidzul Qur’an Aziziyyah.